ARAS Algorithm as Decision Support System's Technique for Selection Student Creativity Program. Issue 1 (1st December 2022) - Abbas, Aries; Masri, Debi; Prayitno, Pungkas; Hasanuddin, H; Zaenuddin, Z; Yuridka, Fitrah; Raharjo, Mokhamad Ramdhani; Anwar, Yohny
Abstract: Indonesia's Directorate General of Higher Education, Ministry of Research, Technology, and Higher Education founded the Student Creativity Program (abbreviated as PKM) to help Indonesian students better understand, develop, and apply the science and technology they learn in class. Public and private university students alike can participate in this important event. Once a proposal has been submitted and reviewed at each institution, the activity moves on to the national level. Students at colleges and universities have the power to select the best proposals to ensure that the best ideas get funded. The choice is made by the research and community service institution (abbreviated as LPPM). LPPM uses qualified reviewers in their respective fields to do the selection. After that, the papers are ranked according to the PKM guidebook's evaluation components, which are listed in the review findings. A comparison method is essential to evaluate proposals because subjective evaluation is severely discouraged. PKM proposal selection will be examined utilizing decision support system methodologies in this study. The problem was solved using the Additive Ratio Assessment (ARAS) approach. Title, Abstract, Preliminary; Destination; Method; Discussion Result; Conclusion; and Bibliography comprise the eight components of the assessment criteria based on 21 samples of PKM proposals. The ARAS technique calculates that nine suggestions are deserving of national selection, with a Ki value ranging from 0.97534518 to 0.70813085.